Applications of X-Chromosome Short Tandem Repeats for Human Identifica-tion: A Review - Aedrianee Reeza Alwi; Naji Arafat Mahat; Faezah Mohd Salleh; Seri Mirianti Ishar; Mohammad Rahim Kamaluddin; Mohd Radzniwan A Rashid (Brawijaya University, 2024)
Indexed by Scopus